Palindromic sequences preceding the terminator increase polymerase III template activity. - Chu, W M (1997)
Four consecutive T residues in the sense strand are sufficient to terminate transcription by RNA polymerase III (pol III). Previously we observed that compared with this minimally sufficient terminator, five T residues immediately preceded by a palindromic sequence increases transcriptional expression both in vitro and in vivo, raising the question of whether a palindromic sequence has a role in pol III termination. Here we observe that site-directed mutations which eliminate the dyad symmetry of the palindromic sequence decrease transcriptional expression. Similar effects are observed whether dyad symmetry is eliminated in regions of the palindrome which are proximal or distal with respect to the terminator. Compensatory mutations at either site to restore dyad symmetry rescue transcriptional activity. These observations suggest that a higher order structure, such as a RNA hairpin, immediately preceding the terminator increases pol III transcriptional activity.